Food supplements in the pediatric population of Serbia: A review of commonly used products - Dabetić, Nevena; Đuričić, Ivana; Ilić, Tijana; Dudašova Petrovičova, Olina; Dodevska, Margarita; Kukić Marković, Jelena; Ivanović, Nevena (Archives of Pharmacy, 2025)
Food supplements (FS) are products intended to provide additional nutrients to the normal diet. They contain concentrated amounts of nutritive and non-nutritive compounds with a nutritional or physiological effects and are available in various dosage forms for ingestion in small, defined quantities. In recent decades, FS have become increasingly popular among children. When developing pediatric products, both the nutritional needs and the safety aspects specific to this population group are considered. This report analyzes dietary supplements used by children in Serbia, focusing on dosage, safety and the existence of official guidelines. The analysis includes vitamins (D, K and B-complex), probiotics, omega-3 fatty acids, beta-glucans and various herbal products. Although these supplements are widely used in Serbia, there are official pediatric guidelines only for vitamin D, vitamin K, probiotics and omega-3 fatty acids. Herbal supplements are particularly problematic due to insufficient data on safety, interactions and possible side effects. Therefore, increased education of both parents and healthcare professionals is essential to ensure appropriate intake, maximize health benefits and support the proper and safe use of supplements in the pediatric population.
Keywords: food supplements; pediatric population; guidelines; vitamins; herbal preparations